Teaching Competencies of Mathematics Teachers in Basista District - Frias, Blue-J R. (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
The main objective of this study was to assess the teaching competencies of mathematics teachers in Basista District, Basista, Pangasinan for the school year 2018-2019. It will seek to answer the following questions: What is the demographic profile of Mathematics teachers with: the highest educational attainment, years in teaching mathematics, and trainings/seminars attended in mathematics? What is the extent of competencies of mathematics teachers assessed by master teacher and school head in: content knowledge and pedagogy, learning environment and diversity of learners, curriculum and planning, assessment and reporting. What is the relationship between the extent of competencies of mathematics assessed by master teacher and principal along with content knowledge and pedagogy, learning environment and diversity of learners, curriculum and planning, assessment and reporting across the demographic profile of mathematics teachers? What are the challenges/problems encountered by the mathematics teachers in teaching the mathematics subject? What development plan can be proposed to enhance the mathematics program? What is the level of validity of the proposed development plan in s mathematics program? This study used the Descriptive-Correlational Research Design. The respondents of this research were one hundred forty-four (144) Mathematics Teachers in Basista District, Basista, Pangasinan, the School Year 2018-2019. Total Enumeration was used. The following conclusions are formed: the majority of the mathematics teachers already earned masteral units. Almost all of the mathematics teachers have long teaching experience teaching the mathematics subject. The majority of the mathematics teachers have few trainings/seminars attended in mathematics. Mathematics teachers in Basista District, Basista, Pangasinan are competent in terms of content knowledge and pedagogy, learning environment and diversity of learners, curriculum and planning, assessment and reporting as assessed by master teachers and principals. The higher the educational attainment of the mathematics teacher, the better competencies they acquire in teaching the mathematics subject. The longer the teaching experience of teachers teaching the mathematics subject, the mastery level of teaching the mathematics subject increase. The more trainings and seminars acquired by the mathematics teacher, the more they can improve their competencies as a mathematics teacher. Overlapping of school activities resulting in insufficient time in teaching mathematics is considered a problem by the mathematics teacher in Basista District. The study recommends the following: Seminars and trainings like INSET, School and District LAC sessions should be provided by the school leaders for mathematics teachers to enhance further their competencies in mathematics. The School Administrators should find ways how to motivate the teachers to improve their crafts and students to love the subject by conducting one-on-one sessions/discussion with teachers and selected students. The Mathematics teachers should be more innovative to get the maximum learning of the students by knowing the behavior, characteristics, and attitude of the students towards the subject. Efforts on time management and coordination of school activities should be monitored by both teachers and administrators to address the problems of mathematics teachers on the overlapping of activities. The Higher School Officials should constantly review and improve policies pertaining to teaching and learning in Mathematics that are suited to the current needs of the teachers and learners. Future researchers should conduct a similar study but to a larger set of respondents and include the participation of the students. Keywords : Teaching Competencies of Mathematics Teachers